ENHANCING WRITING SKILLS THROUGH EDUCATIONAL INNOVATION: INTEGRATING PROJECT-BASED LEARNING AND AUDIOVISUAL MEDIA - Whisnubrata, Antonius Awan Asta Adhiprana; Dimara, Johannes; Tamaela, Kevin Andrea (CV. TOTUS TUUS, 2025)
The low writing proficiency among junior high school students, particularly in remote areas of Indonesia, remains a pressing concern in language education. This research addresses the problem by implementing a Project-Based Learning (PjBL) model supported by audiovisual media to improve students' narrative writing skills. The objective of this study was to analyze the impact of the integrated instructional model on students' writing performance, focusing on idea development, vocabulary usage, and text organization. Using a quantitative, pre-experimental design with a One-Group Pretest-Posttest framework, data were collected from 30 Grade VII students at SMP Antonius Nabire. Writing assessments were conducted before and after the treatment, with results analyzed using paired sample t-tests and normalized gain (N-Gain) scores. The findings revealed a significant improvement in students’ writing abilities after the intervention, with posttest scores exceeding the Minimum Mastery Criteria (KKM) and N-Gain scores indicating high learning gains. These outcomes suggest that combining PjBL with audiovisual media enhances student engagement, creativity, and comprehension in writing tasks. The study contributes to educational research by providing a replicable model for under-resourced contexts, demonstrating that multimodal and student-centered instruction can bridge performance gaps and promote equitable learning. Future research is recommended to examine long-term impacts and scalability of the model across diverse educational settings.